Radiological evaluations of low cost wollastonite nano‐ceramics graft doped with iron oxide in the treatment of induced defects in canine mandible. Issue 7 (1st December 2020) - Mabrouk, Mostafa; Taha, Said K.; Abdel Hamid, Mohamed A.; Kenawy, Sayed H.; Hassan, Elham A.; El‐Bassyouni, Gehan T.
Abstract: Wollastonite with/without maghemite [(Fe2 O3 ), 0, 3 and 10 wt%] was prepared by facile wet precipitation method. Effect of Fe2 O3 presence in the obtained nano‐ceramics on physical structure, morphology, size and the mechanical features was evaluated using X‐ray diffraction, transmission electron microscope, and universal testing machine. Moreover, the in vitro biomineralization was examined using simulated body fluid (SBF) by means of scanning electron microscope/energy dispersive X‐ray, Fourier transform infrared, and inductively coupled plasma. An in vivo study was conducted on 24 adult male mongrel dogs to test the biosafety of fabricated samples in the reconstruction of experimentally induced mandibular bone defects. Bone density was measured through cone beam computed tomography analysis conducted at 1 and 3 months following surgery. Wollastonite was the main phase in all the prepared samples however little maghemite was developed in Fe‐containing samples. No remarkable changes were recognized for physical structure of obtained microcrystalline structures, however, a decrease in particle size was noted in the existence of Fe2 O3 (10‐15 nm) when compared to the pure wollastonite (30–50 nm). Mechanical features were dependent on the included Fe2 O3 concentration within the wollastonite ceramic matrix. The degree of biomineralization of the samples immersed in SBF was elevated with the increase in Fe2 O3 percentage. Clinically, the reconstruction of bone defects was uneventful without any adverse toxic effect. Bone density was significantly increased at 1 and 3 months ( p  < .001) in grafted defects compared to control ones. Increasing the doping concentrations of iron oxide was associated with significant increase ( p  < .001) of bone density in all induced defects. Due to the impressive healing effect of current fabricated nano‐ceramics, they are recommended to be utilized as low cost bone graft alternatives.